PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY(TSTS) PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL: Application Of The Two Stay Two Stray (TSTS) Type Cooperative Learning Model To Three-Variable Linear Equation Systems - Yufita; Rizal, Muh.; Baharuddin (Universitas Tadulako, 2024)
This research aimed to obtain a description the implementation of cooperative learning model of two stay two stray (TSTS) which can improve student learning outcomes in solving questions of three variable linear equation system in the tenth grade SMK Negeri 5 Palu. This type of research is classroom action research that refers to the research design of Kemmis and Mc.Taggart, namely (1) planning, (2) implementation, (3) observation and (4) reflection. This research was conducted in two cycles. This research was carried out by following the steps of the Two Stay Two Stray (TSTS) type of cooperative learning model, namely (1) presenting information, (2) organizing students into study groups, (3) providing LKPD and guiding study groups, (4) two members of each group visit other groups, (5) group members who stay to share information with guests, (6) the two visiting members return to their respective groups and present the results of their visit, (7) one of the groups presents their answers, (8) guide students to conclude learning, (9) give awards. The results showed that the application of the Two Stay Two Stray (TSTS) type of cooperative learning model can improve the learning outcomes of class X TSM A SMK Negeri 5 Palu on the material of three variable linear equation system which is indicated by changes that can be seen based on the final action test, classical learning completeness students experienced an increase from the first cycle of 55% and 75% in the second cycle. The results of the observation of teacher and student activities in cycle I were better in cycle II.